Spatial, Seasonal, and Diel Distribution Patterns of Hemimysis anomala in New York State's Finger Lakes - Brown, M. E.; R. S. Morse; O'Neill, K. (Journal of Great Lakes Research, 2012)
With this contribution, we report on the continued and rapid spread of Hemimysis anomala (Crustacea, Mysidae) to inland waters of New York State within the Laurentian Great Lakes watershed. In the spring and summer of 2010, we detected Hemimysis at multiple locations in Seneca Lake, spanning the lake's 61 km length, and in the Seneca-Cayuga Canal, 7 km downstream of the canal's source at Seneca Lake. We did not detect Hemimysis in any of the other ten Finger Lakes. The pattern of range expansion suggests jump dispersal to Seneca Lake, followed by passive dispersal in the Seneca-Cayuga Canal. This range expansion highlights the potential of this emerging invader to spread throughout the New York State Canal system that links the Great Lakes with the Hudson River watershed and a number of large inland lakes via the Erie Canal and its tributaries. During our nighttime sampling campaign on Seneca Lake, densities of Hemimysis exceeding 2500 ind./m3 were associated with littoral rocky structures, docks, and piers. At a reference site near the source of the Seneca-Cayuga Canal, we observed demographic shifts from an adult-dominated population in early spring to a juvenile-dominated population from late-spring to autumn. We also observed strong nocturnal behavior for all stages, with juveniles rising earlier than adults in the evening and remaining higher in the water column near dawn. These demographic and behavioral characteristics, combined with the extensive hydrogeographic network in the Great Lakes, contribute to the species rapid range expansion and the mechanism of its spread.
Keywords: Dispersal; Finger Lakes; Hemimysis anomala; Invasive species; Vertical migration